Assembly of ultra-high strength steel hollow part by hemming using pre-bent inner sheet. (2017) - Abe, Yohei; Mori, Ken-ichiro; Nakagawa, Kazuma
Abstract: Ultra-high strength steel hollow parts were produced by 3-stage hemming using a pre-bent inner sheet. To prevent fracture of the ultra-high strength steel sheet having small ductility, the edge of the outer sheet in the 3rd stage was bent into a corner with a large radius by the contact with the edge of the inner sheet, and the tensile stress was reduced. An automobile hollow part was assembled by hemming of high strength steel sheets having a tensile strength between 780 and 1180 MPa. The galvanised 980 MPa and 1180 MPa hollow parts by hemming using the pre-bent inner sheet were assembled without fracture, whereas the fracture occurred during hemming using the flat inner sheet. The strength of the hollow part was measured from bending and compression tests. The strength of the hollow part increased with increasing strength of sheet. The force of the hemmed part was larger than that of the welded one. It was found that assembling by hemming is useful for producing ultra-high strength steel hollow parts.